Voice, Choice, and Decision 2 : A Study of Local Basic Service Delivery in Cambodia - World Bank (World Bank, Washington, DC, 2014)
The Voice, Choice and Decision (VCD): a study of local governance processes in Cambodia (VCD1) study, conducted in 2011, led to a set of useful insights into the channels through which citizens are heard in commune level decision-making. It presented the formal and informal framework for, and constraints to, citizens' voicing issues, and the overall downward accountability framework of commune and sangkats in Cambodia. The findings of this exploration provide policy makers, development partners and other stakeholders significantly more detail and in-depth understanding of commune decision-making processes and the engagement of citizens, informing both quantitative studies and the very extensive literature on decentralization reform. Voice, Choice and Decision: local basic service delivery: (VCD2) aims to generate better understanding of the platform for citizen and user voice in basic service delivery by considering, in detail, the nature, scope and role of local agents (committees, institutions, individuals) established to implement sector policies, and to identify any other informal channels for the voice of citizens and users of services. In its final form, the study focuses on developing an understanding of voice and accountability in three sectors, health, education and rural water supply. The research and documentation adopted a common framework to the extent possible, considering, in the first instance, what was intended by policy (the arena, organizations, roles and relationships), and comparing this with the reality on the ground in each of the sectors. This final paper then considers the cross cutting themes, identifying the commonalities and differences between these sectors.